Idiographic Roles of Cooperating Teachers as Mentors in Pre-Service Distance Teacher Education - Koç, Ebru Melek (Elsevier Ltd., 2012)
This study aims to define the roles of cooperating teachers as mentors in the context of distance-learning teacher education. The participants included 358 cooperating teachers who mentored 4th-year student teachers in a Distance English Language Teacher Training Program in Turkey. To determine the roles that were perceived as mentoring roles by the cooperating teachers in the distance practicum, an inventory of 10 primary mentoring functions was constructed. These functions included five primary mentoring roles: 'self-trainer', 'networker, 'social supporter', 'academic supporter', and 'psychological supporter'. The results will contribute to an increased understanding of how cooperating teachers perceive their mentoring roles during distance practicums.
Keywords: Distance teacher education; Co-operating teachers; Mentor roles; Practicum